Was Greek Thought Religious? - Ruprecht, L. author. aut Link
XXIV, 268 p.
Keywords: The Greeks are on trial. They have been for generations, if not millennia, from Rome in the First century, to Romanticism in the Nineteenth. We debate the place of the Greeks in the university curriculum, in New World culture - we even debate the place of the Greeks in the European Union. This book notices the lingering and half-hidden presence of the Greeks in some strange places - everywhere from the U.S. Supreme Court to the Modern Olympic Games - and in doing so makes an important new contribution to a very old debate.